Analysis of Factors Affecting Fishermen Participation in Marine Protected Area East Java - Reny Tiarantika; Anthon Efani (Indonesian Journal of Environment and Sustainable Development, 2021)
The main failure of Marine Protected Areas (MPA) in achieving its objectives is the lack of involvement of users (communities) and stakeholders in the planning and decision-making processes, with unforeseen social consequences. Of course, this is also related to the government-based or community-based Marine Protected Area management system. Management of Marine Protected Areas that do not involve local community participation in governance and management will of course result in low local community perceptions of Marine Protected Areas because it will have an impact on local people's lives, especially related to fishery production and fishermen's household income. Therefore, community participation is considered important in the implementation of Marine Protected Areas. The purpose of this study focuses on the factors that affect the level of participation of fishermen in Marine Protected Areas (MPA). This study used 147 samples of fishermen selected by random sampling. The method used is probit regression. The results showed that the participation rate of community-based MPA was higher than that of government-based MPA. Other findings show that age, education, experience, length of trip, fishing gear, group of fishermen, vessel size have a positive and significant impact on fishermen's decisions to participate in Marine Protected Areas. Keywords: marine protected area, fisherman, participation, probit